Intertrochanteric Fracture of the Femur in an Ankylosed Hip: A Case Report - Devkota, Pramod; Ahmad, Shiraz; Pande, Ketan C. (Revista Brasileira de Ortopedia, 2019)
Intertrochanteric fractures of the femur in ankylosed hips are extremely rare. The aims of the operative management for elderly patients with intertrochanteric fractures are to prevent general complications, to maintain mobility, and to relieve pain. The optimal management to achieve these goals is not clear. The authors present a case of a 74-year-old man with an intertrochanteric fracture of the femur in an ankylosed hip. The fracture was managed surgically with dynamic hip screws and cannulated screws. Two years after the surgery, good union was observed at the fracture, and the patient was ambulating independently.
Keywords: ankylosis; femoral fractures; fracture fixation; hip joint; bone screws